What’s in a name: “Serious”, “Severe”, and “Severe and Persistent - T. Kinter, Kenneth (International Journal of Psychosocial Rehabilitation, 2017)
This paper discusses the origins and use of the terms “serious mental illness”, “severe mental illness”, and severe and persistent mental illness”. It makes an argument against the interchangeability of these terms, as each term has inherent strengths and weaknesses. The article suggests that the language of describing people with mental illness is ever-changing but encourages authors to use consistent language and to consider using language that describes the specific population they are discussing (e.g. people with mental illness, people with psychiatric disabilities).